2022
DOI: 10.3389/fphar.2022.828010
|View full text |Cite
|
Sign up to set email alerts
|

The Blind Spot of Pharmacology: A Scoping Review of Drug Metabolism in Prematurely Born Children

Abstract: The limit for possible survival after extremely preterm birth has steadily improved and consequently, more premature neonates with increasingly lower gestational age at birth now require care. This specialized care often include intensive pharmacological treatment, yet there is currently insufficient knowledge of gestational age dependent differences in drug metabolism. This potentially puts the preterm neonates at risk of receiving sub-optimal drug doses with a subsequent increased risk of adverse or insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 147 publications
(248 reference statements)
0
12
0
Order By: Relevance
“…There are a few reports of anakinra use in early infancy ( 34 , 35 ), and no reported use from birth or in extremely premature neonates. Indeed, drug development in premature neonates more broadly remains a “blind spot” in pharmacology ( 36 ). We considered dose selection a crucial element of this trial, both for safety reasons but also to ensure prospect of direct benefit to participants.…”
Section: Methods and Analysismentioning
confidence: 99%
“…There are a few reports of anakinra use in early infancy ( 34 , 35 ), and no reported use from birth or in extremely premature neonates. Indeed, drug development in premature neonates more broadly remains a “blind spot” in pharmacology ( 36 ). We considered dose selection a crucial element of this trial, both for safety reasons but also to ensure prospect of direct benefit to participants.…”
Section: Methods and Analysismentioning
confidence: 99%
“…25,26 The challenges are even greater for preterm neonates, in whom the maturation timelines of gestational and postnatal age overlap. 27 Thus, the pharmacokinetics of antiretroviral drugs cannot be simply extrapolated from studies in older children, and the optimal dose in neonates must be confirmed through dedicated clinical trials. 28 Studies of neonatal "washout" are an efficient way to gain insight into the neonatal metabolism of drugs before formal neonatal pharmacokinetic dosing trials.…”
Section: What Are the Challenges Specific To Studying Pharmacokinetic...mentioning
confidence: 99%
“…In recent years, the understanding of drug metabolism in the human pediatric population has considerably progressed, but data on preterm neonates remain scarce ( van den Anker and Allegaert, 2021 ). Since enrollment of this vulnerable pediatric subpopulation in clinical studies is restricted by several factors (e.g., difficulty in obtaining informed parental consent, limited possibilities for repeated sampling, and general lack of pediatric trials), little is known about pharmacokinetics (PK) in preterm neonates (i.e., born before 37 weeks of gestation) ( Mørk et al, 2022 ). Understanding the ADME (absorption, distribution, metabolism, and excretion) of drugs in this population is critical, as these patients often require pharmacological treatment to survive ( Mørk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since enrollment of this vulnerable pediatric subpopulation in clinical studies is restricted by several factors (e.g., difficulty in obtaining informed parental consent, limited possibilities for repeated sampling, and general lack of pediatric trials), little is known about pharmacokinetics (PK) in preterm neonates (i.e., born before 37 weeks of gestation) ( Mørk et al, 2022 ). Understanding the ADME (absorption, distribution, metabolism, and excretion) of drugs in this population is critical, as these patients often require pharmacological treatment to survive ( Mørk et al, 2022 ). In addition, the level of prematurity may affect drug-metabolizing enzyme (DME) ontogeny, which is insufficiently assessed in preterm neonates ( Mørk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%